Classical theorems on hyperbolic triangles from a projective point of view - Szilasi, Zoltán (Teaching Mathematics and Computer Science, 2012)
Using the Cayley-Klein model of hyperbolic geometry and the tools of projective geometry, we present elementary proofs for the hyperbolic versions of some classical theorems on triangles. We show, in particular, that hyperbolic triangles have no Euler line.